Harvest effects on density and biomass of Neopicrorhiza scrophulariiflora vary along environmental gradients in the Nepalese Himalayas. Issue 13 (19th June 2019) - Poudeyal, Mukti Ram; Meilby, Henrik; Shrestha, Bharat Babu; Ghimire, Suresh Kumar
Abstract: A surprisingly large number of species potentially threatened by human harvest lack quantitative ecological studies incorporating harvest effects, especially clonal species in the alpine Himalayas. We studied density and biomass variation of a threatened medicinal herb, Neopicrorhiza scrophulariiflora, to examine the effect of harvest on plant performance. The study covered two regions with contrasting harvest situations—one with open‐access and another protected from commercial harvesting. Four populations from each region were compared along an elevation gradient (3, 800–4, 800 m). Also, we conducted in situ interviews with 165 and 38 medicinal and aromatic plant users in open‐access and protected regions, respectively, to assess the collection and use patterns of the target species. The quantity harvested per household for traditional healthcare use was similar in both regions. We found no evidence of trade‐driven collection in the protected region but in the open‐access region a trade‐based annual collection of 35–465 kg dried rhizomes per household had a strong negative effect on both density and biomass. In the protected region, the effect of harvest intensity on plant density was positive for vegetative and negative for reproductive individuals, whereas in the open‐access region, the effect was negative for both vegetative and reproductive individuals. The results indicated that a low harvest intensity had no adverse impact on N. scrophulariiflora populations; however, quantification of the optimum level of harvest remains to be explored. Shrub vegetation appeared to buffer the harvest impact on plant density, possibly through the retention of additional moisture. To maintain population viability, we suggest regulating harvest, for example, by introducing rotational harvest systems, ensuring that a sufficient number of reproductive individuals are left as a source of propagules in each harvested population and that populations are given time to recover between harvests. Abstract : The interaction between human harvest, habitat characteristics, and plant growth strategies is a persistent ecological issue. In the alpine Himalayas, the issue is sparsely explored, particularly for clonal plants commercially harvested from the wild. Hence, in this study we examine density and biomass of Neopicrorhiza scrophulariiflora and its response to harvest depending on vegetation, substrate conditions, and anthropogenic regimes to understand the causal factors involved. Our results indicate that low harvest intensity was acceptable to the plant populations, particularly in an area where exploitation was regulated. Shrubland meadow populations were heavily exploited in one area but appeared more resilient to extraction than other commercially exploited populations. We suggest the development of in situ management regimes and sustainable harvest strategies for long‐term conservation.